Cancer-Associated Fibroblast (CAF) Heterogeneity and Targeting Therapy of CAFs in Pancreatic Cancer - Geng, Xinglong; Chen, Hongze; Zhao, Liang; Hu, Jisheng; Yang, Wenbo; Li, Guanqun; Cheng, Chundong; Zhao, Zhongjie; Zhang, Tao; Li, Le; Sun, Bei (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal disease that typically features a dramatic desmoplastic reaction, especially fibroblasts. The roles of cancer-associated fibroblasts (CAFs) in PDAC have received more attention in recent years. As increasing evidence suggests the heterogeneity of CAFs in PDAC, different CAF subtypes have been shown to support tumor growth, while others suppress cancer proliferation. Myofibrotic CAFs (myCAFs) show alpha-smooth muscle actin (α-SMA)high interleukin-6 (IL-6)low myofibroblastic features, are activated by direct contact with tumor cells, and are located in the periglandular region. Inflammatory CAFs (iCAFs) show α-SMAlow IL-6high inflammatory features, are activated by paracrine factors secreted from tumor cells, and are located away from cancer cells. Antigen-presenting CAFs (apCAFs) show major histocompatibility complex II (MHC II) family genes that are highly expressed. CAFs have also been gradually explored as diagnostic and prognostic markers in pancreatic cancer. Targeted therapy of CAFs in PDAC has gradually attracted attention. With the deepening of related studies, some meaningful positive and negative results have surfaced, and CAFs may be the key to unlocking the door to pancreatic cancer treatment. Our review summarizes recent advances in the heterogeneity, function, and markers of CAFs in pancreatic cancer, as well as research and treatment targeting CAFs in pancreatic cancer.